2021
DOI: 10.1186/s12986-021-00589-6
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin ameliorates liver fibrosis via inhibition of hepatic stellate cells by inducing autophagy and natural killer cell-mediated killing effect

Abstract: Background This study investigated the mechanisms underlying the preventive effect of dihydromyricetin (DHM) against liver fibrosis involving hepatic stellate cells (HSCs) and hepatic natural killer (NK) cells. Methods A carbon tetrachloride (CCl4)-induced liver fibrosis model was established in C57BL/6 mice to study the antifibrotic effect of DHM based on serum biochemical parameters, histological and immunofluorescence stainings, and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 67 publications
3
24
0
Order By: Relevance
“…α-SMA is a marker of HSCs activation, and TGF-β1 is generally considered to be the main hepatic fibrosis-promoting cytokine, and many factors leading to liver disease are related to TGF-β1 in varying degrees ( Dewidar et al, 2015 ). In this study, immunofluorescence staining demonstrated that the positive expression of a-SMA and TGF-β1 were significantly increased in liver tissue by TAA-induced, which was consistent with previous studies ( Mi et al, 2019 ; Zhou et al, 2021 ). The increase in α-SMA and TGF-β1 in turn induced the synthesis and secretion of ECM by HSC, thus aggravating liver fibrosis ( Crosas-Molist et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…α-SMA is a marker of HSCs activation, and TGF-β1 is generally considered to be the main hepatic fibrosis-promoting cytokine, and many factors leading to liver disease are related to TGF-β1 in varying degrees ( Dewidar et al, 2015 ). In this study, immunofluorescence staining demonstrated that the positive expression of a-SMA and TGF-β1 were significantly increased in liver tissue by TAA-induced, which was consistent with previous studies ( Mi et al, 2019 ; Zhou et al, 2021 ). The increase in α-SMA and TGF-β1 in turn induced the synthesis and secretion of ECM by HSC, thus aggravating liver fibrosis ( Crosas-Molist et al, 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…Yi Zeng et al demonstrated a protective effect of dihydromyricetin in improving non-alcoholic steatohepatitis ( Zeng et al, 2020 ). Xi Zhou et al demonstrated that dihydromyricetin attenuated carbon tetrachloride-induced liver injury by modulating autophagy and inhibiting the activation of hepatic stellate cells ( Zhou et al, 2021 ). Ping Qiu et al also demonstrated the protective effect of dihydromyricetin against ethanol-induced liver injury ( Qiu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Male C57BL/6J mice were fed in a condition as previously reported (Zhou et al, 2021). The experimental procedure of each group was illustrated in Figure 1A.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Protein expression was investigated by western blot analysis as in previous methods (Zhou et al, 2021). The primary antibodies were used to study the protein expression of sirtuins-3 (SIRT3, 1: 1000 dilution; Cell Signaling Technology, #2627S), hypoxiainducible factor-1α (HIF-1α, 1:300 dilution; Proteintech,…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Dihydromyricetin (DHM, the structure of which is shown in Figure 1 ), a natural flavonoid extracted from vine tea and other Ampelopsis species, has anti-inflammatory and antioxidant effects and has been proven to inhibit liver fibrosis and diabetic nephropathy ( Liu et al, 2019 ; Zhou et al, 2021 ). However, its effects on pulmonary fibrosis have not been determined.…”
Section: Introductionmentioning
confidence: 99%